The effectiveness of gel hot pack (UP Gelpack) on pain and flexibility over latent myofascial trigger point of upper trapezius muscle - Konsanit, Saisunee; Phrompao, Patcharin; Hongluek, Chakkraphan; Yodthee, Thanawat; Srithawong, Aunrat (Journal of Medical and Public Health Region 4, 2023)
UP Gelpack, a hot gel pack made from tapioca starch, offers excellent heat absorption and energy release properties. It is a safe and convenient option for clinical pain management. This study aimed to compare the effectiveness of UP Gelpack with a standard hot gel pack for pain level and neck flexibility over latent myofascial trigger point of upper trapezius muscle. Thirty-six aged 20-40 years with cervical myofascial pain syndrome were randomly assigned to two groups: UP Gelpack (n=18) and standard hot pack (n=18). Both groups received treatment for a 20-minutes session, three times per week for 2 weeks. Before and after the experiments, the subjects' pain levels and neck flexibility were measured using the visual analog scale (VAS) and active neck range of motion, respectively. Results showed that the VAS scores significantly decreased in both the standard hot pack (from 4.89 ± 1.02 to 4.50 ± 0.71; p < 0.05) and UP Gelpack groups (from 4.78 ± 1.11 to 4.22 ± 0.73; p < 0.05), and neck flexibility significantly increased (neck flexion, lateral flexion to right and left) after both modalities (p < 0.05). However, there were no statistically significant differences between the two groups (p>0.05). In conclusion, both modalities have similar effects on pain reduction and neck flexibility in subjects with neck pain. Thus, UP Gelpack can be considered as an alternative method for treating patients with chronic neck pain at home because it is easy to use and does not cause irritation.